The Canadian Auto Workers: An Inspirational Story - Rinehart, James W. (Monthly Review: An Independent Socialist Magazine, 1998)
The article reviews the book, "The Canadian Auto Workers: The Birth and Transformation of a Union," by Sam Gindin.
Keywords: books

On the Line at Subaru Isuzu: The Japanese Model and the American Worker - Rinehart, James W. (Labour / Le Travail, 1997)
The article reviews the book, "On the Line at Subaru Isuzu: The Japanese Model and the American Worker," by Laurie Graham.
Keywords: AUTOMOBILE industry; BOOKS – Reviews; GRAHAM; Laurie; Nonfiction; ON the Line at Subaru Isuzu: The Japanese Model & the American Worker (Book); United States

Quality of Working Life: Contemporary Cases - Rinehart, James W. (Labour / Le Travail, 1987)
This article reviews the book, "Quality of Working Life: Contemporary Cases," edited by J. B. Cunningham and T. H. White.
Keywords: CUNNINGHAM; J. B.; Nonfiction; QUALITY of Working Life: Contemporary Cases (Book); QUALITY of work life; REVIEWS; WHITE; T. H.; books

Wartime Strikes: The Struggle Against the No-Strike Pledge in the UAW During World War II - Rinehart, James W. (Labour / Le Travail, 1981)
This article reviews the book, "Wartime Strikes: The Struggle Against the No-Strike Pledge in the UAW During World War II," by Martin Glaberman.

Worker Participation and the Politics of Reform - Rinehart, James W. (Labour / Le Travail, 1989)
The article reviews the book, "Worker Participation and the Politics of Reform," edited by Carmen Siriarmi.
Keywords: BRITISH Labour & the Cold War (Book); Labor Unions; Nonfiction; REVIEWS; WEILER; Peter; books

Labor-Management Committees: Confrontation, Cooptation, or Cooperation?; Inside the Circle: A Union Guide to QWL [Quality of Worklife] - Rinehart, James W. (Labour / Le Travail, 1988)
The article reviews two books: "Labor-Management Committees: Confrontation, Cooptation, or Cooperation?," by Charlotte Gold, and "Inside the Circle: A Union Guide to QWL" by Mike Parker

American Jobs and the Changing Industrial Base - Rinehart, James W. (Labour / Le Travail, 1987)
This article reviews the book, "American Jobs and the Changing Industrial Base," edited by Eileen Collins and Lucretia Dewey Tanner.

Worker Commitment and Labour Management Relations Under Lean Production at Cami - Rinehart, James W.; Huxley, Christopher; Robertson, David (Relations industrielles / Industrial Relations, 1994)
CAMI, a unionized Suzuki-General Motors auto plant in Ontario, attempted to construct a workplace characterized by worker commitment and cooperative labor-management relations. These efforts failed. There was a 5-week strike in the Fall of 1992 at the plant. While CAMI was in the start-up mode, labor-management relations were relatively harmonious and the working environment relaxed. With the onset of full production all this changed, and the meaning of "lean" production became clearer. Workers regularly contested the dictates of lean production at CAMI. Interest and participation in quality circle and suggestion programs declined. Proponents of lean production are likely to define CAMI as an aberration by involving the partial implementation thesis or stressing the militancy of the union. In one respect only are they right. The strike does distinguish CAMI as exceptional, at least until there are similar manifestations of industrial conflict in other transplants. However, the conditions that produced the strike appear in unionized as well as non-unionized transplants.
Keywords: AUTOMOBILE industry; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Commitments; Japanese management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strikes; Studies